Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0fo01467b
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of capsaicin and the underlying mechanisms: a review

Abstract: Obesity and overweight have become a serious health problem in the world, which are linked to a varity of metabolic disorders. Phytochemicals with weight-loss effect have been widely studied for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…This is in line with previous in vivo and in vitro reports in different tissues. A study on obese mouse models demonstrated that capsaicin administration promotes mitochondrial function and increased ATP levels in these animals [51]. Moreover, capsaicin appears to also increase glucose metabolism and ATP production in the human intestinal epithelium [10,52].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous in vivo and in vitro reports in different tissues. A study on obese mouse models demonstrated that capsaicin administration promotes mitochondrial function and increased ATP levels in these animals [51]. Moreover, capsaicin appears to also increase glucose metabolism and ATP production in the human intestinal epithelium [10,52].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of capsaicin consumption on the maintenance of a healthy body weight and reduction of adipose tissue have also been observed (Sharma et al, 2013). Preclinical and clinical studies have shown that the potential mechanism of capsaicin's anti-obesity action includes the inhibition of adipogenesis, activation of brown adipose tissue (BAT) and stimulation of thermogenesis, increased lipolysis, decreased appetite, and increased satiety as a result of the regulation of the nervous system in the hypothalamus and modulation of the functions of the digestive system and the intestinal microbiome (Li et al, 2020b;Rosca et al, 2020;Zheng et al, 2017). The main mechanism of action of capsaicin on the metabolism is the activation of TRPV1 (transient receptor potential vanilloid subfamily 1).…”
Section: Capsaicinmentioning
confidence: 99%
“…Randomized clinical trials have shown an association between increased capsaicin intake in the diet and decreased appetite, increased resting energy expenditure, increased fat oxidation, increased BAT activity, and increased thermogenesis (Zheng et al, 2017). In obese subjects, an increase in capsaicin consumption was associated with a decrease in blood glucose, a decrease in tissue insulin resistance, and a favorable lipid profile (Li et al, 2020b). In studies on mice, following the administration of capsaicin, a favorable change in the intestinal microbiota was observed, consisting in the growth of bacteria that synthesize short-chain fatty acids (SCFA) and a reduction in the number of gram-negative bacteria producing LPS (bacterial liposaccharide), which increases the production of pro-inflammatory cytokines (Wang et al, 2020b).…”
Section: Capsaicinmentioning
confidence: 99%
“…Recently, RK has attracted researchers' attention because of its weight‐control application. The motivation for these studies comes from the structural similarity of RK with capsaicin and synephrine, which are known to exert antiobesity effects (Li et al., 2020). In 2005, Morimoto (Morimoto et al., 2005) first elucidated the influence of RK on obesity and demonstrated that RK supplementation decreased body weight gain, hepatic triglyceride content, and the weight of visceral adipose tissue (epididymis, retroperitoneum, and mesentery) in high‐fat diet‐induced obese mice.…”
Section: Health Benefits Of Raspberry Ketonementioning
confidence: 99%